Chemotherapy-induced peripheral neuropathy in patients treated with taxanes and platinum derivatives. (May 2015) - Ewertz, Marianne; Qvortrup, Camilla; Eckhoff, Lise
Abstract Background. Chemotherapy with taxanes and platinum compounds has resulted in substantial survival benefits both in adjuvant and metastatic settings. However, as a side effect, such chemotherapy may cause peripheral neuropathy (CIPN) which may result in discontinuation of treatment, and if it persists after treatment completion, has a negative impact on quality of life (QoL). Results. Symptoms of CIPN are sensory, like pain, numbness, and tingling, typically located in the hands and feet. For oxaliplatin, there is an acute form of CIPN, resulting in paraesthesias in the mouth and throat during or shortly after the infusion triggered by exposure to cold. Risks factors for CIPN include preexisting neuropathy, either from treatment with other neurotoxic agents, or from comorbid conditions. The incidence of CIPN is related to dose per cycle, cumulative dose, and duration of infusion. While cisplatin-induced neuropathy is irreversible, CIPN induced by taxanes may persist for several years in about 30% of patients. Evidence from the literature is suggestive that CIPN is likely to be negatively associated with QoL. No agents have been identified to be recommended for the prevention of CIPN. For treatment of CIPN, the best available data supports a moderate recommendation for treatment with duloxetine and evidence is inconclusive regarding the use of tricyclic antidepressants (such as nortriptyline), gabapentin, and a compounded topical gel containing baclofen, amitriptyline HCL, and ketamine. Conclusion. Research is still needed to predict which patients are at high risk of developing CIPN during treatment and in whom CIPN will persist after completion of chemotherapy.